MADRASAH STUDENTS’ PERCEPTIONS OF THE IMPLEMENTATION OF THE “LOVE CURRICULUM” AS CHARACTER EDUCATION IN BANTEN PROVINCE - Rahimah Rahimah (Adisam Publisher, 2025)
This study aims to describe madrasah students’ perceptions in Serang regarding implementing the Love Curriculum initiated by the Ministry of Religious Affairs of the Republic of Indonesia. The Love Curriculum is an educational approach that emphasizes inculcating values such as compassion, tolerance, empathy, and patriotism in the learning process. The research employed a quantitative method with a survey approach. The sample consisted of 100 randomly selected madrasah students in Serang City. The data collection instrument was a closed-ended questionnaire developed based on students’ perception indicators across four main aspects: love for God, love for others, love for the environment, and love for the homeland. The collected data were analyzed quantitatively and descriptively using percentages and averages. The findings indicate that the majority of students hold positive perceptions toward the implementation of the Love Curriculum in their madrasahs, particularly in the aspects of fostering tolerance and social concern. However, strengthening love for the environment still needs to be improved through learning activities and practical engagement within the school setting. These findings will provide insights for madrasahs and the Ministry of Religious Affairs in formulating more humanistic and inclusive learning policies.